2007
DOI: 10.1002/ange.200602341
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Photon and Three‐Photon Absorption in an Organometallic Dendrimer

Abstract: Dedicated to Professor Gerhard Erker on the occasion of his 60th birthdayMultiphoton absorption is of intense interest for a variety of potential applications, such as optical power limiting, data storage, multiphoton microscopy, microfabrication, and frequency up-conversion lasing.[1] Multiphoton processes possess significant advantages, such as superior resolution, which enables precise spatial control for the various applications, together with the possibility of using infrared lasers at wavelengths that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…For example, the lowest-energy intense transition in the NIR region is ipsochromically shifted by around 343 cm À1 (44 nm) when proceeding from 3-H + to 4 3 + . These modest shifts suggest that a similar assignment can be made for the various absorptions of this compound in its various oxidation states (4,4 3 + , 4 6 + ).…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…For example, the lowest-energy intense transition in the NIR region is ipsochromically shifted by around 343 cm À1 (44 nm) when proceeding from 3-H + to 4 3 + . These modest shifts suggest that a similar assignment can be made for the various absorptions of this compound in its various oxidation states (4,4 3 + , 4 6 + ).…”
mentioning
confidence: 57%
“…A dark-brown solid was again isolated that exhibits the same cyclic voltammogram as 3-HA C H T U N G T R E N N U N G [PF 6 ] but distinct spectral signatures (IR, UV/ Vis/NIR, and Mçssbauer). The isolated sample proved even more reactive than 4 ], which again limited its study in solution, although its UV spectrum was qualitatively similar to that observed in the OTTLE cell following dioxidation of 3-H. The IR spectrum of the isolated solid sample indicates the presence of a strong absorption at 1947 cm À1 and a second, weaker, band near 1845 cm À1 , which might be attributed to the two n CC stretches expected for this compound.…”
Section: Optical Electron Transfer In 3-mentioning
confidence: 85%
See 2 more Smart Citations
“…photon absorbers [37][38][39][40][41] Three-photon absorption cross-section is exceptionally strong for this organic molecule: . It is higher than those for best performing inorganic quantum dots 3-photon absorbers6 and 2 orders of magnitude higher than those for organic conjugated systems ( Figure 5).…”
Section: Figure 5 3-photon Absorption Cross-section Of Qot2 In Compamentioning
confidence: 99%